Vasoprotective effects of lysophosphatidic acid inhibit vascular injury caused by SARS-CoV-2 infection - Fumitaka Muramatsu; Naoi Hosoe; Tatsuya Suzuki; Teppei Shimamura; Yumiko Hayashi; Kazuhiro Takara; Lamri Lynda; Anna Shimizu; Weizhen Jia; Yoshimi Noda; Nobuyuki Takakura; Toru Okamoto; et al. (Scientific Reports)
Abstract Vasculitis and vascular injury are induced in coronavirus disease 2019 (COVID-19) patients, suggesting an association between multi-organ failure and sequelae. Vascular endothelial dysfunction induced by severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) disrupts vascular barrier function, activates coagulation pathways, and induces extravasation of inflammatory cells. In addition to employing standard anti-inflammatory and antiviral agents, using treatments that stabilize and protect blood vessels following SARS-CoV-2 infection is a potentially effective strategy to relieve COVID-19 severity. Here, we focused on the vasoprotective effects of lysophosphatidic acid (LPA), a lipid mediator with diverse activities, and investigated whether it could be a novel therapeutic for COVID-19. Three-dimensional cultures of various human vascular endothelial cells that form luminal structures showed increased expression of LPA4 and entry receptors for SARS-CoV-2 infection, mimicking blood vessels in vivo. Validation using this culture system showed that LPA attenuated SARS-CoV-2 infection-induced vascular destruction and the activation of inflammatory signaling. In experiments with infected animals, LPA administration protected blood vessels and suppressed inflammation and vascular damage in lung tissue. The activation of LPA signaling in vascular endothelial cells may be an effective therapeutic approach for mitigating vascular injury in COVID-19.